Οι αθλητικοί αγώνες της Αρχαίας Μακεδονίας - Αλμπανίδης Ευάγγελος; Αναστασίου Αθανάσιος; Σχοινάς Κωνσταντίνος; Μουρατίδης Ιωάννης (Μακεδονικά, 2011)
The aim of this study is to collect and process data concerning the origin and development of Games in ancient Macedonia through the end of Imperial times. Literary evidence, coins and inscriptions were used as primarysources. During pre-Christian times, Games were held in honour of gods,mostly Zeus (Olympia of Dion, Basilia), Artemis (Amphipolis) and deities,such as Hercules (Heraclia of Thassos). During Imperial times, Games wereheld in honour of gods and deities. God of honour was Zeus, in whose honour Olympia were still held, in Beroia, and Apollo, in whose honour thePythia were held in Thessalonica. Macedonian cities, during the Imperialera, mainly organised Games to honor Roman emperors; emperors honoredby means of Games were Heliogabalus, Philippus the Arab and mainlyGordianus III. In most cases they added to already existent Games the nameof the honored emperor, or changed the names of Games to satisfy the emperors themselves. Of course, these Games were either occasional or of alimited lifetime. The establishment of these Games was the result of both theRoman emperors’ policy and the local authorities’ aspirations